Phraseological stable combinations and their practical application in idiomatic expressions on the examples of the works of Theodor Dreiser (Eurasian Journal of Learning and Academic Teaching, 2022)
Phraseology is a branch of the science of language that studies stable combinations of words. Phraseologism is a stable combination of words, or a stable expression. Used to name objects, signs, actions. It is an expression that arose once, became popular and entrenched in the speech of people. The expression is endowed with figurativeness, it can have a figurative meaning. Over time, the expression can take on a broad meaning in everyday life, partially including the original meaning or completely excluding it. The phraseological unit as a whole has lexical meaning. The words included in the phraseological unit separately do not convey the meaning of the entire expression. Phraseological units can be synonymous (at the end of the world, where the raven did not bring bones) and antonymous (lift up to heaven - trample into the dirt). Phraseologism in a sentence is one member of the sentence.